Indonesia’s Cultural Diplomacy on the Conduct of Indonesian Language for Foreigners Programme in Thailand (2014-2019) - Inova Collins; Isyana Adriani; Muhammad Sigit Andhi Rahman (Insignia: Journal of International Relations, 2020)
Abstract This article examines the Indonesian language for Foreigners Programme (Bahasa Indonesia bagi Penutur Asing or BIPA) implementation in the internationalisation of the Indonesian language in Thailand. Based on Law No.24 of 2009 Article 44, the Government of Indonesia has a task to develop the role of the Indonesian language at the international stage. This effort has gained momentum recently with the establishment of the ASEAN Economic Community (AEC), where ASEAN citizens including Thais are encouraged to have foreign language skills. Thailand is one of the gateways to Southeast Asia. Many businesses and tourists come to Thailand first and then continue to other Southeast Asian nations. This condition encourages Thai people to learn foreign languages, including the Indonesian language. This article utilises a qualitative approach method, particularly interview and observation as a data collection method, and uses the concept of cultural diplomacy as the theoretical framework. It examines the content of BIPA books, the classroom learning process, and alumni’s feedback toward the programme. The research findings show the high effectiveness of BIPA programme in Thailand. Moreover, BIPA becomes a means of Indonesia's cultural diplomacy, where the Indonesian language and culture serve as tools in creating Thai people's interest in Indonesia. Key Words: BIPA, Cultural Diplomacy, Indonesia, Internationalisation of Indonesian Language, Thailand Abstrak Makalah ini meneliti pelaksanaan program pengajaran ‘Bahasa Indonesia bagi Penutur Asing’ (BIPA) dalam proses internasionalisasi Bahasa Indonesia di Thailand. Berdasarkan UU No. 24 tanggal 2009 Pasal 44, Pemerintah Indonesia memiliki tugas untuk mengembangkan peran bahasa Indonesia di panggung internasional. Upaya ini telah mendapatkan momentum baru-baru ini dengan ditetapkannya Komunitas Ekonomi ASEAN (AEC), dimana warga negara ASEAN termasuk warga Thailand didorong untuk memiliki kemampuan berbahasa asing. Thailand adalah salah satu pintu gerbang penting ke Asia Tenggara. Para pebisnis dan wisatawan datang ke Thailand dulu dan kemudian melanjutkan ke negara Asia Tenggara lainnya. Kondisi ini mendorong orang Thailand untuk belajar bahasa asing, termasuk bahasa Indonesia. Penelitian ini menggunakan metode pendekatan kualitatif, terutama wawancara dan observasi sebagai metode pengumpulan data, dan menggunakan konsep diplomasi budaya sebagai kerangka teoritisnya. Makalah ini meneliti konten buku pengajaran BIPA, proses pembelajaran kelas, dan umpan balik alumni terhadap program. Temuan penelitian menunjukkan tingkat efektivitas yang tinggi dalam pelaksanaan program BIPA di Thailand. Selain itu, BIPA menjadi sarana diplomasi budaya Indonesia, di mana bahasa dan budaya Indonesia menjadi perangkat diplomasi dalam menciptakan ketertarikan rakyat Thailand terhadap Indonesia. Kata Kunci: Internasionalisasi Bahasa Indonesia, BIPA, Diplomasi Budaya, Indonesia, Thailand